Do illegitimate tasks matter for registered nurses' work motivation? A cross-sectional study based on a nationally representative sample of Swedish nurses - Carina Ahlstedt; Linda Moberg; Emma Brulin; Anna Nyberg (Elsevier, 2023)
Background: A challenge in Western countries is the growing need for registered nurses (RNs') in hospitals, primary care and home healthcare. Decreasing illegitimate tasks and strengthening RNs' work motivation are some strategies to address this challenge. Objective: Our overall aim was to explore the association between RNs' experiences of illegitimate tasks and work motivation operationalised as four dimensions: work engagement, opportunities to provide high-quality care, employer satisfaction and intention to remain at the workplace. To address this aim, three specific research questions were asked: (1) Is there an association between illegitimate tasks and work motivation? (2) Do the levels of reported illegitimate tasks differ between RNs working in hospitals and those working in primary care or home healthcare settings? (3) Do associations between illegitimate work tasks and work motivation differ with type of workplace? Design: A cross-sectional design. Methods: We used responses from a stratified population of RNs in Sweden, n = 2,333, working either in hospitals, primary care or home healthcare. Calibrating weights were applied in all analyses to ascertain the generalisability of the findings. Illegitimate tasks were measured with the Bern Illegitimate Tasks Scale. Data were analysed using chi-squared tests and linear or logistic regression analysis. Interaction was measured on the multiplicative scale by adding an interaction term to the fully adjusted models. Results: Overall, approximately 25 % of RNs reported frequently experiencing illegitimate tasks. There were statistically significant associations between higher perceptions of illegitimate tasks and lower ratings in the four dimensions of work motivation: work engagement [beta coefficient [beta] = -0.14, confidence interval [CI] 95 % = -0.18; -0.10], opportunities to provide high-quality care [beta = -0.46, CI 95 % = -0.51; -40] and employer satisfaction [beta = -0.60, CI 95 % = -0.67; -0.54]. Experiencing higher levels of illegitimate tasks also related to a decreased intention to remain at the workplace [illegitimate tasks: odds ratio = 0.32, CI 95 % = 0.27; 0.29]. RNs who worked in home healthcare reported higher levels of illegitimate tasks than RNs who worked in hospitals. Conclusions: Reducing the amount of illegitimate tasks may contribute to counteracting the shortage of RNs by increasing work motivation and willingness to remain at the workplace.